KOMPLEMEN SERUM C3C DAN LIMFOSIT T-CD4+ DARAH - I. Komang Parwata; Endang Retnowati; Betty Agustina Tambunan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
The incidence of HIV and AIDS infection continues to increase despite various treatments have been applied, thus the mortality rate remains high. The examination of CD4+ T lymphocytes number to determine the immune status and the monitoring of therapy has some limitations in facilities and personnel examination as well as expensive costs. The decrease in CD4+ T lymphocytes number will be followed by an increase in the virus number and complement activation, so that the C3c complement levels will decrease. The purpose of this study was to know the correlation between C3c complement serum levels and CD4+ T lymphocytes number in stage I HIV-infected patients by determining them. This research is an observational cross-sectional study. Thirty samples of stage I HIV-infected patients at the UPIPI of Dr. Soetomo Hospital were included in this study; they were collected between July and August 2011. HIV diagnosis was confirmed by positive HIV test results using three different methods. The CD4+ T lymphocytes number were examined using flowcytometry (FACS Calibur, Becton Dickinson (BD) Diagnostics) and complement C3c using Radial Immunodiffusion (NOR Partigen * C3c, Siemens). The results of complement C3c serum levels and CD4 + T lymphocytes number were analyzed with Pearson’s correlation and regression test (Pearson Product Moment Correlation) and Spearman’s Correlation test. The majority (83.33%) of C3c complement levels in stage I HIV-infected patients was still within normal limits (0.55 g/L up to 2.01 g/L; mean 1.39 g/L, SD 0.313 g/L) while the majority of CD4+ T lymphocytes absolute number (80%) were decreased (24-567 cells/μL; mean 295 cells/μL, SD 177 cells/μL). Based on a percentage value of CD4+ T lymphocytes, the majority (86.67%) decreased (2.54-29.48%; mean 13.58%, SD 6.7%). In this study was found that no significant correlation exists between C3c complement and CD4+ T lymphocyte absolute number with p=0.130 and percentage with p=0.217. There was no significant correlation of C3c complement and CD4+ T lymphocyte. This means that C3c complement examination can not be used to predict CD4+ T lymphocytes number.